Trader Participation in Disclosure: Implications of Interactions with Management - Elliott, W. Brooke; Grant, Stephanie M.; Hobson, Jessen L.; Asay, Scott (Contemporary Accounting Research, 2020)
ABSTRACT Technological advances are creating a shift in the information disclosure environment allowing more investors to interact with management. We examine three key levels of trader‐management interaction to assess the accuracy of traders' market‐tested value estimates and resulting market price. These data require an engaging experiment and a complex, contextually rich asset, which we create by playing a popular gaming app before the experiment. Participants view financial information, ask management questions, estimate value, and trade. We find that receiving non‐personalized question responses improves trader estimates of value and market price efficiency relative to when traders ask questions but do not expect a response. This occurs because traders exert more effort estimating value and trading. However, receiving personalized versus non‐personalized responses harms value estimates and market efficiency. This occurs because traders receiving personalized responses fixate on the interaction with management, dividing their attention and diverting it away from valuing and trading the asset.